PENGARUH PEMBERIAN AIR KELAPA DAN PUPUK UREA TERHADAP HASIL DAN PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Itang Bagus Candra Tyasa (grafting, 2021)
The purpose of this study was to determine the effect of dosing fertilizer, coconut water and the interaction of the two on the growth and yield of mustard plants. The design of this study used randomized block design (RBD) there were 2 factors repeated 3 times. The first factor is coconut water with a content of 3: 125 ml / plot, 250 ml / plot and 275 ml / plot. The second factor is urea with a content of 4 g / polybag, 2.02 g / polybag, 4.03 g / polybag, and 6.03 g / polybag. The results showed that: There was a real interaction with the combination of coconut water and urea in mustard plants. The best combination was found in the treatment of 250 ml/plot of coconut water and urea 4.03 gr/polybag (A2U2) which affected the weight of mustard plants with the highest yield of 137.66 g.